Desire on the Inside: Incarcerated bisexual women, identity, and human connection - Smoyer, Amy; Harvey, Rebecca (Queering Desire: Lesbians, Gender and Subjectivity, 2024)
Queering Desire explores, with unprecedented interdisciplinary scope, contemporary configurations of lesbian, bi, queer women’s, and non-binary people’s experiences of identity and desire. Taking an intersectional feminist and trans-inclusive approach, and incorporating new and established identities such as non-binary, masculine of centre (MOC), butch, and femme, this collection examines how the changing landscape for gender and sexual identities impacts on queer culture in productive and transformative ways. Within queer studies, explorations of desire, longing, and eroticism have often neglected AFAB, transfeminine, and non-binary people’s experiences. Through 25 newly commissioned chapters, a diverse range of authors, from early career researchers to established scholars, stage conversations at the cutting edge of sexuality studies. Queering Desire advances our understanding of contemporary lesbian and queer desire from an inclusive perspective that is supportive of trans and non-binary identities. This innovative interdisciplinary collection is an excellent resource for scholars, undergraduate, and postgraduate students interested in gender, sexuality, and identity across a range of fields, such as queer studies, feminist theory, anthropology, media studies, sociology, psychology, history, and social theory. In foregrounding female and non-binary experiences, this book constitutes a timely intervention.
Keywords: dept.mft; dept.swk; peer-reviewed

Queer youth in family therapy - Harvey, Rebecca G.; Fish, Linda Stone (Family Process, 2015)
Trends in popular belief about same-sex relationships have undergone noteworthy change in the United States over the last decade. Yet this change has been marked by stark polarizations and has occurred at varying rates depending upon regional, community, racial, religious, and individual family context. For queer youth and their families, this cultural transformation has broadened opportunities and created a new set of risks and vulnerabilities. At the same time, youth's increasingly open and playful gender fluidity and sexual identity is complicated by unique intersections of class, race, religion, and immigration. Effective family therapy with queer youth requires practitioner's and treatment models that are sensitive to those who bear the burden of multiple oppressions and the hidden resilience embedded in their layered identities. We present case examples of our model of family therapy which addresses refuge, supports difficult dialogs, and nurtures queerness by looking for hidden resilience in the unique intersections of queer youths' lives. These intersections provide transformational potential for youth, their families and even for family therapists as we are all nurtured and challenged to think more complexly about intersectionality, sexuality, and gender. Las tendencias en la creencia popular acerca de las relaciones entre personas del mismo sexo han sufrido un cambio considerable en Estados Unidos durante la ultima decada. Sin embargo, este cambio se ha producido a ritmos diferentes segun las comunidades locales y regionales, y el contexto familiar individual. En el caso de los jovenes queer y sus familias, esta transformacion cultural ha ampliado oportunidades y creado un nuevo conjunto de riesgos y vulnerabilidades. Los jovenes queer y sus familias, al intentar desarrollarse en numerosos contextos, estan marcados por divergencias crueles en actitudes y creencias. Al mismo tiempo, la fluidez del genero y la identidad sexual cada vez mas abiertas y ludicas de los jovenes estan complicadas por intersecciones unicas de clase, raza, religion e inmigracion. Una terapia familiar eficaz con jovenes queer exige modelos de tratamiento y profesionales que sean sensibles a aquellas personas que cargan sobre sus espaldas numerosas opresiones y una resiliencia oculta incorporada en sus identidades multiples. Presentamos ejemplos de casos de nuestro modelo de terapia familiar que aborda el refugio, respalda los dialogos dificiles y apoya la sexualidad alternativa buscando la resiliencia oculta en las intersecciones unicas de las vidas de los jovenes queer. Estas intersecciones ofrecen posibilidades transformacionales para los jovenes, sus familias e incluso los terapeutas familiares mientras nos estimulan y nos desafian a todos a pensar de forma mas compleja acerca de la interseccionalidad, la sexualidad y el genero.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-905-145-849-804 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Adolescent; Family Relations; Family Therapy; Family therapy; Female; Gay; Gender Identity; Homosexuality; Homosexuality; Female; Homosexuality; Male; Humans; Interpersonal Relations; Lesbian; Male; Resilience; Social Identification; Social Isolation; Transgender Persons; Transgendered youth; United States; Vulnerable Populations; Young Adult; adolescent; dept.mft; family relation; family therapy; female; gender identity; homosexuality; human; human relation; lesbianism; male; male homosexuality; procedures; psychology; social behavior; social isolation; statistics and numerical data; transgender; vulnerable population; young adult

Nurturing Queer Youth: Family Therapy Transformed - Stone Fish, Linda; Harvey, Rebecca G. (Norton, 2005)
Keywords: Case studies; Case studies; Gay youth; Counseling of; Bisexual youth; Counseling of; Family psychotherapy; Family relationships; Gay youth; dept.mft; faculty_collection

“To feel him love me”: Emerging intersections of identity, queerness, and differing ability - Harvey, Rebecca (Gender, sex, and sexuality among contemporary youth, 2017)
AbstractOriginality/value This paper provides an alternative approach to nurturing queer identity by (1) creating refuge for emerging sexualities; (2) allowing for difficult dialogues where ability, sexuality, and gender can be pragmatically discussed, performed, and negotiated; (3) tolerating the discomfort of these difficult dialogues and pushing through to nurturing the unique queerness that evolves out of these conversations; and finally (4) encouraging transformation of all participants including client and practitioners. The practitioners discuss their own transformation through the co-created dialog with each other and with the client.
Keywords: Disability; Gay; Gay couple; Intersectionality; Queer; dept.mft; dept.swk

Sexual Identity Development and Heteronormativity - Harvey, Rebecca; Stone-Fish, Linda; Levatino, Paul (The Handbook of Systemic Family Therapy, 2020)
Sexual identity development has traditionally been theorized about from within heteronormative societies founded on patriarchal notions with links to misogyny, racism, and classism, among others. These forms of domination have constrained the way sexual identity has been conceived of, researched and written about within the mental health fields and limited the efficacy of clinical work with all people but especially sexual minorities and those who are gender non-binary. In this chapter the authors will deconstruct heteronormativity, examine the deleterious effect of it on mental health, and locate the influence of intersections of oppression on the field of SFT theory and in clinical work. An LGBTQI (lesbian, gay, bisexual, transgender, questioning, intersex) affirmative clinical framework developed from systems theory and queer theory will be outlined, and then a case study using the framework will be described.
Section: 22 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781119788393.ch22
Keywords: LGBTQI; dept.mft; dept.swk; family therapy; heteronormativity; marriage and family therapy; sexual identity; systemic family therapy

Handbook of LGBTQ-Affirmative Couple and Family Therapy - Harvey, Rebecca; Murphy, Megan J.; Bigner, Jerry J.; Wetchler, Joseph L. (Routledge, 2021)
This comprehensive second edition inspires therapists to utilize clinical work to pragmatically address intersectional oppressions, lessen the burden of minority stress, and implement effective LGBTQ affirmative therapy. A unique and important contribution to LGBTQ literature, this handbook includes both new and updated chapters reflecting cutting-edge intersectional themes like race, ethnicity, polyamory, and monosexual normativity. A host of expert contributors outline the best practices in affirmative therapy, inspiring therapists to guide LGBTQ clients into deconstructing the heteronormative power imbalances that undermine LGBTQ relationships and families. There is also an increased focus on clinical application, with fresh vignettes included throughout to highlight effective treatment strategies. Couple and family therapists and clinicians working with LGBTQ clients, and those interested in implementing affirmative therapy in their practice, will find this updated handbook essential.
Keywords: dept.mft

Lesbian couples - Stone Fish, Linda; Harvey, Rebecca (Encyclopedia of couple and family therapy, 2017)
Keywords: Current Political Climate; Difficult Dialogue; Donor Insemination; LGBTQ Community; Lesbian Couple; dept.mft

Theory into research practice: reflections and recommendations on collaborative feminist research - Harvey, Rebecca G.; Brown, Kristina S.; Miller, Bobbi J.; Williams-Reade, Jacqueline; Tyndall, Lisa; Murphy, Megan J. (Journal of Feminist Family Therapy, 2016)
Six women faculty came together to research their peers asking other women in COAMFTE-accredited programs about their personal and professional identities. The goal of this research was to develop recommendations for the field of Couple/Marriage and Family Therapy to support the engagement and advancement of women faculty. The research collaboration itself became a heuristic, feminist praxis, a co-creation of insight, support network, and professional relationships which had liberating results for the collaborators. We intended to create a research project that would be collaborative, empowering, and transformative for participants; in the process, the collaboration became empowering and transformative for ourselves. This article will reflect on our experiences and provide recommendations for future feminist research teams. Copyright © Taylor & Francis Group, LLC.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00155 tex.type: [object Object]
Keywords: clinical article; collaboration; dept.mft; family therapy; female; feminism; feminist research; gender; human; insider/outsider; marriage; university